We have

\begin{align*} y&= e^{2x}\sin^2 x\\ &= e^{2x}\left(\frac{1-\cos 2x}{2}\right)\\ &= \frac{e^{2x}}{2} - \frac{e^{2x}\cos 2x}{2} \end{align*}


\begin{align*} y^{(n)} &= \left(\frac{e^{2x}}{2}\right)^{(n)} - \left(\frac{e^{2x}\cos 2x}{2}\right)^{(n)}\\ &= 2^{n-1}e^{2x} - \left(\frac{e^{2x}\cos 2x}{2}\right)^{(n)} \end{align*} I don't know how to proceed with the rightmost term. So far I've been applying the Leibniz Rule whenever I've had to find the $n$ derivative of a function of the form $f(x)g(x)$, because is clear that either $f(x)$ or $g(x)$ has a derivative a $k$ derivative ($1<k<n$) equal to zero, which simplifies the expression nicely.

But here

$$\frac{e^{2x}\cos 2x}{2}$$

both functions are infinitely differentiable on $\mathbb{R}$ which makes things a bit different.

My only attempt was to write its n derivative in this form

\begin{align*} &=\frac{1}{2}\sum_{k=0}^n{n \choose k} \big(2^k e^{2x}\big)\bigg(2^{n-k}\cos \left[2x + \frac{\pi(n-k)}{2}\right]\bigg)\\ &=\sum_{k=0}^n {n \choose k} 2^{n-1}e^{2x}\cos \left[2x + \frac{\pi(n-k)}{2}\right] \end{align*}


\begin{align*} y^{(n)} &= 2^{n-1}e^{2x} -\sum_{k=0}^n{n \choose k} 2^{n-1}e^{2x}\cos \left[2x + \frac{\pi(n-k)}{2}\right]\\ &= 2^{n-1}e^{2x}\left(1 -\sum_{k=0}^n{n \choose k} \cos \left[2x + \frac{\pi(n-k)}{2}\right]\right) \end{align*}

But the textbook's answer is

$$2^{n-1}e^{2x}\left(1 -2^{n/2}\cos \left[2x + \frac{\pi n}{4}\right]\right)$$

For some reason I have the feeling that a little of modular arithmetic has to be applied on $\frac{\pi(n-k)}{2}$

  • $\begingroup$ There is a missing binomial coefficient in the summation. I've posted a way forward. $\endgroup$ – Mark Viola Nov 21 '16 at 20:41
  • $\begingroup$ @Dr.MV Ups!. I fixed that (: $\endgroup$ – Jazz Nov 21 '16 at 20:54

You're correct that Leibniz's Rule is a sound way forward. Note that we have

$$\begin{align} e^{2x}\sin^2(x)=\frac12 e^{2x}-\frac12 e^{2x}\cos(2x) \end{align}$$

Then, taking the $n$'th order derivative, we have

$$\begin{align} \frac{d^n}{dx^n}\left(e^{2x}\sin^2(x)\right)&=\frac{d^n}{dx^n}\left(\frac12 e^{2x}-\frac12 e^{2x}\cos(2x)\right)\\\\ &=2^{n-1}e^{2x}-\frac12 \sum_{k=0}^n\binom{n}{k}\frac{d^{n-k}e^{2x}}{dx^{n-k}}\frac{d^k\cos(2x)}{dx^k}\\\\ &=2^{n-1}e^{2x}\left(1-\sum_{k=0}^n\binom{n}{k}\frac{d^k\cos(2x)}{d(2x)^k}\right)\\\\ \end{align}$$

So, the problem boils down to taking the $k$'th derivative of the cosine function. But we can express that derivative as $\cos(x+k\pi/2)$. Hence, we have

$$\begin{align} \frac{d^n}{dx^n}\left(e^{2x}\sin^2(x)\right)&=2^{n-1}e^{2x}\left(1-\sum_{k=0}^n\binom{n}{k}\cos(x+k\pi/2)\right)\\\\ &=2^{n-1}e^{2x}\left(1-\text{Re}\left(\sum_{k=0}^n\binom{n}{k}e^{i(x+k\pi/2)}\right)\right)\\\\ &=2^{n-1}e^{2x}\left(1-\text{Re}\left(e^{ix}(1+i)^n\right)\right)\\\\ &=2^{n-1}e^{2x}\left(1-\text{Re}\left(2^{n/2}e^{i(x+n\pi/4)}\right)\right)\\\\ &=2^{n-1}e^{2x}\left(1-2^{n/2}\cos(x+n\pi/4)\right)\\\\ \end{align}$$

as was to be shown!

  • $\begingroup$ What a clever way to do it. It never crossed my mind to take this approach. Thanks!! $\endgroup$ – Jazz Nov 21 '16 at 20:57
  • $\begingroup$ You're welcome! My pleasure. -Mark $\endgroup$ – Mark Viola Nov 21 '16 at 21:02
  • $\begingroup$ I have a little doubt (:. How from here $\frac{\mathrm{d}^k\cos(2x)}{\mathrm{d}x^k}$ one goes to $\frac{\mathrm{d}^k\cos(2x)}{\mathrm{d}(2x)^k}$?. I've been trying to do the step in between, but I' not getting it. I passed this $2^k$ from $2^{n-k}$, which is obtained by expanding $\frac{\mathrm{d}^{n-k}e^{2x}}{\mathrm{d}x^{n-k}}$, to the side of the cosine and then multiplied and divided the last factor by $2$, to get this $\frac{2^{k+1}}{2}\frac{\mathrm{d}^k\cos(2x)}{\mathrm{d}x^k}$. Certainly in the denominator we get $\mathrm{d}(2x)^k$ but I'm not able to get $\mathrm{d}^k\cos(2x)$ $\endgroup$ – Jazz Nov 21 '16 at 21:32
  • $\begingroup$ From the $nxk$'th derivative on $e^{2x}$, we get a factor $2^{n-k}$, and from the $k$,th derivative on $\cos(2x)$, we get a factor $2^{k}$. Multiplying these leave $2^n$, which is independent of the index of summation. $\endgroup$ – Mark Viola Nov 21 '16 at 21:53

Calculate the fist few derivatives and see if a recognizable pattern shows up.

$f(x) = \frac {e^{2x}}{2} + \frac {e^{2x}\cos2x}{2}\\ f'(x) = e^{2x} + e^{2x} \cos 2x - e^{2x}\sin 2x\\ f''(x) = 2e^{2x} - 2e^{2x}\cos 2x - 2e^{2x}\sin 2x - 2e^{2x}\sin 2x - 2e^{2x} \cos 2x = 2e^{2x} - 4e^{2x}\sin 2x\\ f'''(x) = 4e^{2x} - 8 e^{2x}\sin 2x - 8 e^{2x}\cos 2x\\ f^{(4)} = 8e^{2x} - 16\cos 2x$

Do you see a pattern? Can you prove that the pattern will continue?

If you know a little bit about complex exponential you could say:

$f(x) = \frac {e^{2x}}{2} + Re[\frac {e^{(2+2i)x}}{2}]\\ f^{(n)}(x) = 2^n\frac {e^{2x}}{2} + \frac {(2\sqrt2)^n}{2} Re[\frac {e^{(2+2i)x + \frac {n\pi}{4}i}}{4}]\\ f^{(n)}(x) = 2^n\frac {e^{2x}}{2} + \frac {(2\sqrt2)^n}{2} e^{2x} \cos(2x + \frac {n\pi}{4})\\$


We know that $$\sin^2(x) = \dfrac{1 - \cos(2x)}{2}= \dfrac{1}{2} -\dfrac{1}{2}\Re(\exp(2ix)), $$ where $\Re$ is the real part of a complex number.

It follows that

$$y =\exp(2x)\sin^2(x) = \dfrac{\exp(2x)}{2} - \dfrac{1}{2}\Re(\exp(zx)), $$ with $z = 2+2i.$

Using complex-valued derivatives:

$$\dfrac{dy}{dx} = \exp(2x)- \dfrac{z}{4}\exp(zx)- \dfrac{z^{*}}{4}\exp(z^{*}x),$$ which leads to

$$\dfrac{d^ny}{dx^n} = 2^{n-1}\exp(2x) - \dfrac{z^n}{4}\exp(zx) - \dfrac{z^{*n}}{4}\exp(z^{*}x) = 2^{n-1}\exp(2x) - \dfrac{1}{2}\Re (z^n \exp(zx)).$$


The crux of the problem boils down to computing the $n$th derivative of the function $f(u)=e^u\cos u$. (Note that if $g(x)=f(2x)$, then $g^{(n)}(x)=2^nf^{(n)}(2x)$.) Using $\cos u=\Re(e^{iu})$ and $1+i=\sqrt2e^{i\pi/4}$, we find

$$f(u)=\Re(e^{(1+i)u})\implies f^{(n)}(u)=\Re((1+i)^ne^{(1+i)u})=2^{n/2}e^u\Re(e^{(u+n\pi/4)i})=2^{n/2}e^u\cos\left(u+{n\pi\over4}\right)$$

Applied to the OP's problem, we have

$$y(x)={e^{2x}\over2}-{f(2x)\over2}\implies y^{(n)}(x)={2^ne^{2x}\over2}-{2^nf^{(n)}(2x)\over 2}=2^{n-1}e^{2x}\left(1-2^{n/2}\cos\left(2x+{n\pi\over4} \right)\right)$$


Taking into consideration just the second part, let's call $$p(x)=e^{2x}\cos 2x$$ then \begin{align} &p^{(1)}(x)=2e^{2x}\cos 2x-2e^{2x}\sin 2x\\ &p^{(1)}(x)=2e^{2x}(\cos 2x-\sin 2x)=2e^{2x}\sqrt{2}\left(\frac{\sqrt{2}}{2}\cos 2x-\frac{\sqrt{2}}{2}\sin 2x\right)\\ &p^{(1)}(x)=2^{3/2}e^{2x}\left(\cos(\pi/4)\cos 2x-\sin(\pi/4)\sin 2x\right)\\ &p^{(1)}(x)=2^{3/2}e^{2x}\cos\left( 2x+\pi/4 \right) \end{align} and following the same calculation that we just did we can conclude that $$p^{(2)}(x)=2^{3/2}2^{3/2}e^{2x}\cos\left( 2x+\pi/4+\pi/4 \right)$$ Now we can see the pattern. So we can prove by finite induction that $$p^{(n)}(x)=2^{3n/2}e^{2x}\cos\left( 2x+n\pi/4\right)$$ and finaly: $$\left(\frac{e^{2x}\cos 2x}{2}\right)^{(n)}=2^{3n/2-1}e^{2x}\cos\left( 2x+n\pi/4\right)$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.